Intramedullary nailing versus plating in shaft humerus fractures: a prospective randomized study - Pansey, Nachiket Kailash; Sharma, Gaurav Mahesh; Naik, Lokesh Gudda; Badgire, Krishna Sudhakar; Qureshi, Faisal; Jain, Vikas (International Journal of Research in Orthopaedics, 2017)
Introduction- The two most commonly used modalities of internal fixation in fracture shaft of humerus are Plate osteosynthesis and Intramedullary nailing. The present study aims to analyze and compare both the techniques in terms of functional and radiological outcome. Material and Methods- 43 patients with diaphyseal fracture humerus were treated with Intramedullary nailing and plating between March 2015 and March 2016. The inclusion criteria were patients with closed diaphyseal fracture humerus. Compound fractures, pathological fractures, Non-union, mal-union fractures were excluded from the study. Results- 22 (51.2%) cases were operated using the antegrade nailing technique whereas dynamic compression plating was done in 21 (48.8%) cases. The mean age was 42±4.2 years. Road traffic accident was the most common mechanism of injury with 29 (67.5%) cases. 12-A2 type of fracture pattern were most common involving 23 (53.5%) cases. The mean surgical time was 68 mins in cases where nailing was done and 115 mins in cases with plating (P<0.001). Radiological union was seen at 13±4.8 weeks and 15±3.9 weeks in the nailing and plating group respectively. There were 2 (9.09%) cases in the nailing group and 1 (4.7%) case in the plating group which had delayed union. 3 (13.6%) cases in the nailing group had post-operative shoulder stiffness. The mean ASES score at the end of one year was 31.3 in nailing and Background: The two most commonly used modalities of internal fixation in fracture shaft of humerus are plate osteosynthesis and intramedullary nailing. The present study aims to analyze and compare both the techniques in terms of functional and radiological outcome. Methods: 43 patients with diaphyseal fracture humerus were treated with Intramedullary nailing and plating between March 2015 and March 2016. The inclusion criteria were patients with closed diaphyseal fracture humerus. Compound fractures, pathological fractures, non-union, mal-union fractures were excluded from the study. Results: 22 (51.2%) cases were operated using the antegrade nailing technique whereas dynamic compression plating was done in 21 (48.8%) cases. The mean age was 42±4.2 years. Road traffic accident was the most common mechanism of injury with 29 (67.5%) cases. 12 A2 type of fracture pattern were most common involving 23 (53.5%) cases. The mean surgical time was 68 minutes in cases where nailing was done and 115 minutes in cases with plating (P <0.001). Radiological union was seen at 13±4.8 weeks and 15±3.9 weeks in the nailing and plating group respectively. There were 2 (9.09%) cases in the nailing group and 1 (4.7%) case in the plating group which had delayed union. 3 (13.6%) cases in the nailing group had post-operative shoulder stiffness. The mean ASES score at the end of one year was 31.3 in nailing and 29.6 in plating group (P =0.327). There were 37 (86.5%) cases with excellent to good results. Conclusions: Nailing and plating have equal functional outcomes in cases with shaft humerus fracture. 29.6 in plating group (P=0.327). There were 37 (86.5%) cases with excellent to good results. Conclusion- Nailing and plating have equal functional outcomes in cases with shaft humerus fracture.